2006
DOI: 10.1007/s00464-006-9042-6
|View full text |Cite
|
Sign up to set email alerts
|

Are transverse colon cancers suitable for laparoscopic resection?

Abstract: Laparoscopic resection of transverse colon cancers is technically feasible and not associated with a significantly higher rate of complications or conversions or with impaired oncologic outcomes compared with patients having segmental laparoscopic resections for other colon cancers. Operating time is longer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 7 publications
(7 reference statements)
0
55
1
1
Order By: Relevance
“…Our results contrasted with those reported by some laparoscopic experts. [20][21][22] Laparoscopically assisted resection of transverse colon cancer was reported to take significantly longer in terms of operative time than laparoscopically assisted resection of cancer at other sites 20,21 or conventional open surgery 22 for transverse colon cancer; although reports 23,24 from Korea show that no significant difference was found in such comparisons. In addition, 2 study groups 20,21 suggested that laparoscopically assisted resection of transverse colon cancer may have an insignificant higher rate of postoperative complications, which should not be ignored and may be a reflection of the greater complexity associated with the resection of transverse colon, compared with other less challenging segmental colectomies.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Our results contrasted with those reported by some laparoscopic experts. [20][21][22] Laparoscopically assisted resection of transverse colon cancer was reported to take significantly longer in terms of operative time than laparoscopically assisted resection of cancer at other sites 20,21 or conventional open surgery 22 for transverse colon cancer; although reports 23,24 from Korea show that no significant difference was found in such comparisons. In addition, 2 study groups 20,21 suggested that laparoscopically assisted resection of transverse colon cancer may have an insignificant higher rate of postoperative complications, which should not be ignored and may be a reflection of the greater complexity associated with the resection of transverse colon, compared with other less challenging segmental colectomies.…”
Section: Discussionmentioning
confidence: 50%
“…[20][21][22] Laparoscopically assisted resection of transverse colon cancer was reported to take significantly longer in terms of operative time than laparoscopically assisted resection of cancer at other sites 20,21 or conventional open surgery 22 for transverse colon cancer; although reports 23,24 from Korea show that no significant difference was found in such comparisons. In addition, 2 study groups 20,21 suggested that laparoscopically assisted resection of transverse colon cancer may have an insignificant higher rate of postoperative complications, which should not be ignored and may be a reflection of the greater complexity associated with the resection of transverse colon, compared with other less challenging segmental colectomies. When our minilaparotomy series is compared with recently reported series of laparoscopically assisted resection in terms of operative time, blood loss, and postoperative complications, the mean operative time (133.5 minutes) is markedly shorter in our minilaparotomy series than those (203.6-260 minutes) [20][21][22][23][24] of reported laparoscopically assisted series, and the blood loss and the incidence of postoperative complications seem to be compatible to or smaller than those of laparoscopically assisted series.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…There have been three reports of laparoscopic -assisted transverse cancer resection, supporting its feasibility, since 2007 26,27) . Kim et al 27) published a comparative study on the short -term clinico -pathologic outcomes of LAC (n = 37) vs. OC (n = 50) for transverse colon lesions.…”
Section: Transverse Colon Cancermentioning
confidence: 99%
“…[1][2][3] However, the impact of several factors, such as obesity and transverse colon cancer, on the outcomes of laparoscopic colectomy poses some technical problems. [4][5][6][7] Patients with transverse colon cancer were often excluded from previous randomized controlled trials because it was difficult to determine the appropriate extent of lymph node dissection, and because the technical difficulties depend on the identification and lymph node dissection around the middle colic vessels, which have a variable anatomy. [5][6][7][8][9] The recent development of multidetector computed tomography (MDCT) has made it possible to perform three-dimensional CT angiography (3DCTA).…”
mentioning
confidence: 99%